2021
DOI: 10.1021/acs.jmedchem.1c00933
|View full text |Cite
|
Sign up to set email alerts
|

4-Methyl-1,2,3-Triazoles as N-Acetyl-Lysine Mimics Afford Potent BET Bromodomain Inhibitors with Improved Selectivity

Abstract: The bromodomain and extra terminal (BET) protein family recognizes acetylated lysines within histones and transcription factors using two N-terminal bromodomains, D1 and D2. The protein−protein interactions between BET bromodomains, acetylated histones, and transcription factors are therapeutic targets for BET-related diseases, including inflammatory disease and cancer. Prior work demonstrated that methylated-1,2,3triazoles are suitable N-acetyl lysine mimetics for BET inhibition. Here we describe a structure−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…GSK778, a potent pan-D1 inhibitor, was reported by Gilan et al The pyrrolidinyl group interacts with a nonconserved Asp on D1s (His on D2s) via a water-bridged hydrogen bond (Figure A,B) . Similar interactions were found by our recently reported triazole-based inhibitors, including DW34 , which exhibit pan-D1 selectivity, with the exception of a high affinity interaction with BRD4 D2 (Figure A,C) . Meanwhile, pan-BD2 inhibitors have been developed, including RVX-208, ABBV-744, and GSK046, and are effective in different disease models.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…GSK778, a potent pan-D1 inhibitor, was reported by Gilan et al The pyrrolidinyl group interacts with a nonconserved Asp on D1s (His on D2s) via a water-bridged hydrogen bond (Figure A,B) . Similar interactions were found by our recently reported triazole-based inhibitors, including DW34 , which exhibit pan-D1 selectivity, with the exception of a high affinity interaction with BRD4 D2 (Figure A,C) . Meanwhile, pan-BD2 inhibitors have been developed, including RVX-208, ABBV-744, and GSK046, and are effective in different disease models.…”
Section: Introductionsupporting
confidence: 85%
“…Affinities reduced sharply when polar ether or hydroxyl groups were installed ( 16 , 17 , 18 ). These results indicated that the aryl groups on the imidazole scaffold form significant hydrophobic interactions with the WPF shelf, which was not observed in our triazole-based inhibitor series …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations